Recovery of right ventricular function after intermediate-risk pulmonary embolism: results from the multicentre Pulmonary Embolism International Trial (PEITHO)-2 - Mavromanoli, Anna; Barco, Stefano; Ageno, Walter; Bouvaist, Hélène; Brodmann, Marianne; Cuccia, Claudio; Couturaud, Francis; Dellas, Claudia; Dimopoulos, Konstantinos; Dürschmied, Daniel; Empen, Klaus; Faggiano, Pompilio; et al. (Clinical research in cardiology, 2023)
Right ventricular (RV) function plays a critical role in the pathophysiology and acute prognosis of pulmonary embolism (PE). We analyzed the temporal changes of RV function in the cohort of a prospective multicentre study investigating if an early switch to oral anticoagulation in patients with intermediate-risk PE is effective and safe.